2014
DOI: 10.1007/s40089-014-0110-y
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Fano resonances in bimetallic layered nanostructures

Abstract: Plasmonic Fano resonances arise in bimetallic layered nanostructures (metal-dielectric-metal and dielectric-metal-dielectric-metal) are studied theoretically as the function of their geometrical parameters. Multiple Fano resonances are generated in these nanostructures where several subradiant dark modes appear due to the geometrical symmetry breaking induced by offsetting different layers. The plasmonic responses of the proposed nanoparticles with equal volumes are compared and multiple Fano resonances with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Other plasmonic bimetallic layered nanostructures like ring/disk nanocavities (RDNC) [14,31,36] and double nanoshell structure (DNS) [9] exhibit the similar superradiant mode, subradiant mode, and single dipole Fano resonance in the concentric case. For the achievement of multiple Fano resonances in RDNC and DNS nanostructures, the same symmetry breaking conception is used [10,14,37]. The symmetry reduced metal nanostructures are usually fabricated using complex and expensive techniques, which severely reduces their application potentials.…”
Section: Comparison With Other Plasmonic Nanostructuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Other plasmonic bimetallic layered nanostructures like ring/disk nanocavities (RDNC) [14,31,36] and double nanoshell structure (DNS) [9] exhibit the similar superradiant mode, subradiant mode, and single dipole Fano resonance in the concentric case. For the achievement of multiple Fano resonances in RDNC and DNS nanostructures, the same symmetry breaking conception is used [10,14,37]. The symmetry reduced metal nanostructures are usually fabricated using complex and expensive techniques, which severely reduces their application potentials.…”
Section: Comparison With Other Plasmonic Nanostructuresmentioning
confidence: 99%
“…Recently, these resonances are studied in all types of plasmonic nanosystems due to the potential applications in metamaterials, surface-enhanced Raman spectroscopy (SERS), sensing, and slow-light devices [2][3][4][5][6][7]. These nanostructures include nanoshells [8][9][10][11], nanocones [12,13], ring/disk nanocavities [14][15][16], dimers [17][18][19], trimers [20], and nanoparticle aggregates [21,22], where the Fano resonance arises from the destructive interference of symmetric bright mode with the asymmetric dark plasmon mode.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In plasmonic nanosystems, EIT and Fano resonances usually originate from the destructive interference of a narrow band and broad band spectra, which results in a sharp asymmetric line shape [9][10][11][12][13][14][15][16][17][18]. The line shape of such resonances is highly sensitive to the local dielectric medium and geometry of the nanoparticle.…”
Section: Introductionmentioning
confidence: 99%
“…He observed that destructive and constructive interferences take place due to the overlapping of a discrete state with a continuum state, which results in the asymmetric profile. Over the past few years, plasmonic nanosystems have been investigated for the generation of Fano resonances with sharp dispersion [2][3][4][5][6][7][8][9][10][11][12]. In such systems, Fano resonance arises due to the spectral overlapping of broad superradiant and narrow subradiant plasmon modes, which are usually characteristics of dipolar and higher-order plasmon modes, respectively.…”
Section: Introductionmentioning
confidence: 99%